Characterisation of isocitrate dehydrogenase gene mutant WHO grade 2 and 3 gliomas: MRI predictors of 1p/19q co-deletion and tumour grade. Issue 10 (October 2021) - Doig, D.; Kachramanoglou, C.; Dumba, M.; Tona, F.; Gontsarova, A.; Limbäck, C.; Jan, W.
Abstract : AIM: To identify imaging predictors of molecular subtype and tumour grade in patients with isocitrate dehydrogenase (IDH) gene mutant (IDHmut ) World Health Organization (WHO) grade 2 or 3 gliomas. MATERIALS AND METHODS: Patients with histologically confirmed WHO grade 2 or 3 IDHmut gliomas between 2016 and 2019 were included in the study. Magnetic resonance imaging (MRI) images were evaluated for the presence or absence of potential imaging predictors of tumour subtype, such as T2/fluid attenuated inversion recovery (FLAIR) signal match, and these factors were examined using regression analysis. On perfusion imaging, the maximum relative cerebral blood volume (rCBVmax ) was evaluated as a potential predictor of tumour grade. The performance of two experienced neuroradiologists in correctly predicting tumour type on MRI was evaluated. RESULTS: Eighty-five patients were included in the study. The presence of T2/FLAIR signal match >50% of tumour volume ( p< 0.01) and intratumoural susceptibility ( p= 0.02) were independent predictors of 1p/19q co-deletion. Mean rCBV max was significantly higher in WHO grade 3 astrocytomas ( p= 0.04) than WHO grade 2 astrocytomas. The consensus prediction of 1p/19q co-deletion status by two neuroradiologists of tumour was 95% sensitive and 86% specific. CONCLUSION: The presence of matched T2/FLAIR signal could be used to identify tumour subtype when biopsy is inconclusive or genetic analysis is unavailable. rCBVmax predicted astrocytoma grade. Experienced neuroradiologists predict tumour subtype with good sensitivity and specificity. Highlights: Radiological features of low grade glioma could identify tumour subtype. Astrocytoma grade was predicted by the maximum rCBV on perfusion imaging. Experienced neuroradiologists accurately predicted low grade glioma tumour subtype.